Kinerja Pengelolaan Persampahan dalam Mendukung Penataan Kawasan Permukiman Kumuh: A Systematic Literature Review - Raihannisa Fitri; Heni Fitriani; Febrian Hadinata (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Despite the growing body of research on solid waste management and slum settlement upgrading, existing studies remain fragmented, limiting a comprehensive understanding of the factors influencing waste management performance. This study synthesizes current evidence and develops a conceptual framework of waste management performance in supporting sustainable slum upgrading through a Systematic Literature Review (SLR). Following the PRISMA 2020 guidelines, 50 peer-reviewed articles published between 2015 and 2025 were systematically selected and analyzed using thematic synthesis. The findings identify five key dimensions influencing waste management performance: technical and operational support, management effectiveness, institutional and regulatory capacity, financial sustainability, and community participation. The effectiveness of these dimensions is moderated by socio-economic conditions, settlement characteristics, governance capacity, and policy implementation, explaining variations in waste management outcomes across regions. The study's novelty lies in integrating these determinants into a comprehensive conceptual framework that explains how waste management performance contributes to environmental quality improvement and sustainable slum settlement upgrading. The proposed framework enriches the theoretical understanding of integrated waste management while providing evidence-based guidance for policymakers and urban planners in designing adaptive, integrated, and sustainable waste management strategies.